CLINICAL AND IMMUNOLOGICAL SUBSTANTIATION OF THE PROBIOTIC MEDICINE APPLICATION TO PREVENT THE EXACERBATIONS OF THE CHRONIC ADENOIDITIS AMONG CHILDREN - S.S. Antonova; V.V. Botvin'eva; L.S. Namazova (Union of pediatricians of Russia, 2007)
The article deals with the effects of the probiotic medicine among the patients, suffering from chronic adenoiditis. The researchers have received some reliable improvement of the nasal breathing and decrease of the adenoid vegetations. More over, the children showed normal immunological indices: IgG level, general IgE and interleukin 4 (Il 4). in over 90% of cases, the researchers were able to avoid any surgical treatment of adenoids, by replacing it with a painless, safe and efficient, conservative method.Key words: interleukins, Ige, procalcitonin (pct), cortisol, adenoiditis.